Exploring confidence development in interprofessional teams: A pre-post analysis of a health and social care education module - Sharron Blumenthal; Sivaramkumar Shanmugam; Jamie McDermott; John Locke; Tamsin Fitzgerald; Christopher Duncan; Kareena McAloney-Kocaman; Lindsey Burns (PLoS ONE, 2025)
Aim Confidence can be defined as a strong belief, firm trust, or sure expectation in relation to achieving an outcome. The study aimed to examine change in confidence to collaborate in teams in undergraduate health and social care students undertaking a mandatory 6-week IPE module using the Team Observed Professional Encounter (TOSPE). Method A pre-test post-test study was undertaken. Confidence was measured using the validated Interprofessional Education Academic Behavioural Confidence Scale. Independent t-tests and Analysis of Variance were used to establish differences between groups at the commencement of the study. To compare pre and post confidence scores paired t-tests were used for normally distributed data, and Wilcoxon signed rank test were undertaken for non-normally distributed data. Cohen’s d and Pearson r were produced as measures of effect size. A mixed design Analysis of Variance was conducted to examine the influence of categorical variables on changes in confidence scores. Results Data were included from 80 matched pairs. Pre-test self-perceived scores for Total Confidence and the subscales for Interprofessional Team Working, Interprofessional Communication and Behaviours Underpinning Collaboration increased significantly (p = < .001) post module completion. Changes in scores demonstrated large effect sizes for total confidence (d = .888), Interprofessional Team Working (d = .872), Interprofessional Communication (d = .945) and a medium effect size for Behaviours Underpinning Collaboration (r = .534). Time was found to be the only categorical variable that had a significant effect on confidence (p < 0.05). Conclusion Post-intervention student confidence increased significantly for total confidence and all subscales of the IPE ABC scale. When considering between subject effects only time was found to demonstrate significant results indicating an association between the IPE intervention and increased self-perceived confidence. However, it should be noted that other factors such as small subgroup sample size, social desirability response bias and potential overconfidence bias may impact the results observed, so caution in interpretation of the results considering these limitations are advised. This study adds to the body of literature that suggests IPE interventions impact positively on behaviours that underpin collaborative practice.